Herpetofaunal diversity in Manaslu Conservation Area, Nepal - Pokhrel, Ganesh Kumar; Thakuri, Sudeep (Our Nature, 2017)
Herpetofauna is the least studied subject in the Nepal Himalaya. Most of the studies in wildlife are focused on mammals and birds. This paper presents the results of the herpetofauna survey in Manaslu Conservation Area in the Central Nepal, conducted with the aim of establishing the baseline on herpetofauna species diversity. The study recorded 16 species of herpetofauna, indicating a highly potential abundance of herpetofauna in the region. The study is first of its kind in establishing the baseline. The information, thus, obtained can be useful for implementing a biodiversity monitoring activities, and current and future conservation efforts. The study also underlines a need of an extensive study of herpetofauna in this region. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.